2022
DOI: 10.3389/fonc.2022.990841
|View full text |Cite
|
Sign up to set email alerts
|

Development of D-α-Tocopherol polyethylene glycol 1000 succinate fabricated nanostructural lipid carrier of sorafenib tosylate for metastatic colorectal targeting application: Stability, physical characterization, cytotoxicity, and apoptotic studies against SW48 cells PTEN

Abstract: The study aimed to create D-α-Tocopherol polyethylene glycol 1000 succinate (TPGS) nanostructured lipid carriers (NLC) of sorafenib tosylate (ST) as lymphatic delivery systems (LDDS) to fight Metastatic colorectal cancer. Initially, ST-SLN, ST-NLC, and ST-LNE were formulated considering oleic acid (OA), glycerol monolinoleate (GMO), glycerol monolinoleate (GML) as solid lipid and further characterised, and tested for stability. The most stable ST-NLC was fabricated with TPGS to produce ST-TPGS-NLC and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…This report is in accordance with report published by few other researchers. There have been several reasons for drug resistance in cancer cell including cell death inhibition, changes in drug target, target gene amplification, mutation in transporters and decreased cellular drug uptake (Bin Emran et al, 2022;Mansoori et al, 2017). Li Y and coworkers reported that spherical NPs have higher cellular uptake ability of drug (Li et al, 2015).…”
Section: In Vitro Drug Releasementioning
confidence: 99%
See 1 more Smart Citation
“…This report is in accordance with report published by few other researchers. There have been several reasons for drug resistance in cancer cell including cell death inhibition, changes in drug target, target gene amplification, mutation in transporters and decreased cellular drug uptake (Bin Emran et al, 2022;Mansoori et al, 2017). Li Y and coworkers reported that spherical NPs have higher cellular uptake ability of drug (Li et al, 2015).…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…It have been successfully utilized in nanoparticles development and reported for biocompatible and nontoxic with cell and tissues (Alsaab et al, 2022; Ayyanaar et al, 2019). D‐Alpha Tocopheryl Polyethene glycol succinate extensively being used as permeation enhancer, emulsifier and solubilizer in nanoformulations development (Bhattacharya et al, 2022; Kumbhar et al, 2022). So, in this research, we established a technique that effectively targets RLX loaded poly (lactic‐co‐glycolic acid) (PLGA) nanoparticles to drug‐resistant BC cells along with suitable combination of co‐surfactants such as Didodecyl dimethyl ammonium bromide and D‐Alpha Tocopheryl Polyethene glycol succinate.…”
Section: Introductionmentioning
confidence: 99%